1991
DOI: 10.1126/science.254.5037.1467
|View full text |Cite|
|
Sign up to set email alerts
|

Subterranean Waterworks of Biblical Jerusalem: Adaptation of a Karst System

Abstract: Ancient Jerusalem has long been known to possess a system of subterranean waterworks by which the spring of Gihon, which issues outside the walls, could be approached from within the city, and its waters diverted to an intramural pool. Most scholars regarded these waterworks as man-made, but the techniques of underground orientation and ventilation employed by the builders, as well as the numerous anomalies and ostensible mistakes in design, mystified investigators. Geological investigation has revealed the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…This rationale appealed to many others [1e4, 26,27,30,31] because it seemed to solve the above-mentioned enigmas with one simple theory. In a well-known publication in the journal 'Science' Gill [27] expanded KH and concluded that ST (as well as other waterworks beneath ancient Jerusalem) 'was fashioned essentially by skillful enlargement of natural (karstic) dissolution channels'. If true, KH implies that ST is not a special technical achievement, but rather an elegant adaptation of a natural feature.…”
Section: The Siloam Tunnelmentioning
confidence: 98%
See 1 more Smart Citation
“…This rationale appealed to many others [1e4, 26,27,30,31] because it seemed to solve the above-mentioned enigmas with one simple theory. In a well-known publication in the journal 'Science' Gill [27] expanded KH and concluded that ST (as well as other waterworks beneath ancient Jerusalem) 'was fashioned essentially by skillful enlargement of natural (karstic) dissolution channels'. If true, KH implies that ST is not a special technical achievement, but rather an elegant adaptation of a natural feature.…”
Section: The Siloam Tunnelmentioning
confidence: 98%
“…Gill [26,27] suggested that an original karst conduit was followed and totally obliterated by subsequent hewing. Our survey of many kilometers-long cave passages around Jerusalem [14,18,20,21] shows that the cross section varies significantly along each passage.…”
Section: Geological Structurementioning
confidence: 99%
“…However, Iron Age underground construction became more generalized with large underground storage and water supply systems. An example is the 700 m of tunnelling underneath old Jerusalem (Gill 1991(Gill : 1467. Construction of artificial caves for funerary purposes became widespread and their functional use continued until the beginning of Christianity, as demonstrated by the Holy Sepulchre in Jerusalem (Broshi 1991: 83).…”
Section: Underground Burial Chamber Traditionmentioning
confidence: 99%
“…In the Surata of the flies of the Koran, the impiety of the inhabitants of that kingdom made it disappear because of water, the same element that had allowed its prosperity. 8 Even today, Israel carefully monitors its water supply and only a powerful interconnected network is able to meet its needs. The Palestinian entity will quickly face the lack of water and, therefore, its dependence on the Hebrew state.…”
Section: Introductionmentioning
confidence: 99%